The benefits and physiological changes of high intensity interval training - Soeria Santoso, Dewi Irawati; Boenyamin, Hafizh Ahmad (Faculty of Medicine, Trisakti University, 2019)
Physical inactivity have been linked with many major non-communicable diseases and as many as 27.5% of adults globally are considered inactive. Physical activity has been proven to be beneficial in the prevention of many chronic diseases and may reduce the risk of premature death. High intensity interval training (HIIT) has been gaining popularity as a time-efficient alternative for regular exercise training. Current studies show that HIIT is more efficient in improving cardiorespiratory fitness, increasing insulin sensitivity and reducing blood pressure than moderate intensity continuous training (MICT). The advantage of HIIT in fat loss compared to MICT is still unclear, but HIIT might be more efficient in the obese population. The effect of HIIT on increasing aerobic fitness could be caused by increase in stroke volume due to the increase in cardiac contractility, capillary density and mitochondrial adaptation. Fat loss during HIIT could be caused by increased fat oxidation and elevated hormones that drive lipolysis and reduce appetite. While vigorous physical activity may transiently increase the risk of cardiac events. The effect of HIIT on increasing aerobic fitness could be caused by increase in stroke volume due to the increase in cardiac contractility, increased of capillary density and mitochondrial adaptation. While fat loss during HIIT could be caused by an increased fat oxidation, elevated hormones that drives lipolysis and reduces appetite. While vigorous physical activity may transiently increase the risk of cardiac event. High intensity interval training is generally safe even in the elderly population and in people with coronary heart disease.